CLASS STRUGGLE AS A REACTION TOWARD THE SOCIAL CONDITION IN CAPITALIST SOCIETY AS REFLECTED IN GEORGE BERNARD SHAW’S PYGMALION - Tuaderu, Yohanes (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Class struggle is a collective reaction of the workers toward the inhumane treatments applied by the capitalists. The collectiveness creates group awareness of the workers as an exploited ‘class’. This awareness, in turn, stimulates working class struggle to oppose the capitalists’ pressure and exploitation. By employing sociological approach, Pygmalion – a play of five acts written by George Bernard Shaw – is considered as one of the literary pieces of the early twentieth century that portrays the social condition of British society at the era when capitalism reached its height. Shaw himself is a socialist who supports the working class struggle through propaganda, public lectures, critical essays, and literary works that attack the human exploitation in industrial sphere.This is a qualitative research using Marxist criticism which is theorized by various scholars to analyze the struggle of Liza Doolittle – the main character in Pygmalion –as the portrait of the unstopped struggle of the working class to have their rights which are deliberately ignored by the capitalists. This theory is considered as the most appropriate instrument to analyze Shaw’s masterpiece, Pygmalion, since Shaw himself is a well-known British socialist who strived for the social reform indicated by the presence of democracy, the admission of human rights, the just distribution of social welfare, and the reasonable respect to individual freedom.This research found that the social condition in England in the end of 19th century to the early 20th century was mostly affected by the practice of human exploitation in industrial environment. This conditions caused dehumanization and serious poverty suffered by the working class. Class struggle, then, became a spirit that generated the laborers to free themselves from poverty, to release themselves from the capitalists’ oppression, and to gain the admission that they are equal with other human beings in society.